Democracy, Development and Industrial Policy in Nigeria: A Historical Contextualisation. Issue 169 (1st December 2021) - Gaiya, Abel B.S.
Abstract: The article places Nigeria's political and economic challenges in historical and global context. As opposed to viewing democracy or development emerging simply as the 'will of the people' or 'political will', it encourages a historical and structural view of the phenomena. Sustained democratic institutions and intensive economic growth emerge under particular conditions where the continued maintenance of hegemony and gate-keeping extractive states are no longer viable. A diversified capitalist class and economic power among a strong middle class are needed to demand greater democratic accountability. Industrial policy is essential to creating the structural change required for their emergence. Yet the dispersed and ethno-religiously fragmented distribution of power makes industrial policy implementation difficult. Given the salience of such historical and structural forces, postcolonial Nigerians should be seen as formative generations. Students and practitioners of development economics, policy and politics should be more creative in producing politically informed policies for the country.